أحكام التلاوة، مخارج الحروف وصفاتها، ( المادة المنهجية للصفوف المتوسطة في العراق إنموذجا) (Journal of the College of Basic Education, 2025)
This research deals with the necessity of commitment to reciting the Holly Quran in the correct manner, and not being negligent in doing so, because doing any mistake in reciting the Holy Quran is not acceptable even if it is unintentional, by studying the Islamic books for the intermediate stages in Iraqi schools, especially Provisions of Recitation. Detailing in Articulations and Descriptions of letters; we go deep in, to make it easier for the beneficiary to understand and assimilate the provisions smoothly and in a logical sequence. In writing the research, I followed the descriptive analytical method. I enumerated the methodological material present in the book on the stage in question, then presented my observations on it, from both two sides: the theoretical and the scientific sides. Then I have the application of the rules of Recitation of the letters, the Articulations and Descriptions of letters. The research concluded with important recommendations for teachers, students, and those responsible for managing the academic subjects, such as the importance of focusing on the etiquette of reciting the Holy Quran, and the necessity of generalizing it for all books that deal with The Holy Quran. And the necessity of redistributing methodological materials in intermediate stage Islamic books in a way that ensures the correct consequence for the subjects, and the useful benefits for students. In addition to that, the importance of studying Articulations and Descriptions of the letters, because it explains the reasons of sounding a letter like this, so it makes it easier to understand how a letter is made.